When “Beyond-Human” is “Becoming-Human”: An Ustopian Paradox in Margaret Atwood’s Oryx and Crake - Bakshi, Amrita (Interconnections / Interconnexions)

(untitled) (Posthumanism Research Institute, 2026)
This article explores Margaret Atwood’s Oryx and Crake as a critical site for interrogating posthumanist ontology and biotechnological futurity. Engaging Chien-Hung Chen’s theorization of “becoming-human” in the Anthropocene and Atwood’s own term “ustopia,” the essay examines how Crake’s ecotopian vision—a genetically reengineered humanity purged of aggression and desire—unravels into a recursive dystopia. Despite their engineered docility, the Crakers evolve symbolic consciousness and ritual, reintroducing anthropocentric hierarchies through myth and narrative. Snowman’s manipulative storytelling reinscribes human power dynamics, complicating the supposed rupture from Homo sapiens. Drawing on Freud, Darwin, and biopolitical critique, the paper argues that posthuman subjectivity cannot escape the ethical and symbolic infrastructures of the human. Oryx and Crake thus becomes a posthuman parable, where attempts to transcend human flaw reinstantiate it, destabilizing linear notions of progress and exposing the entangled fictions of species, power, and survival.